RETRACTED: Organization of seed breeding activities for leguminous crops and introduction of new varieties in conditions of piedmont and mountainous zones of Armenia - Matevosyan L.G.; Barbaryan A.A.; Ghukasyan A.G.; Ghazaryan R.G.; Alikhanyan N.A.; Shaboyan G.G. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001